2022
DOI: 10.3390/en15249560
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Combustion Process for Two Refuse-Derived Fuel (RDF) Streams Using Statistical Methods and Heat Recovery Simulation

Abstract: This study characterises materials that belong to the group of refuse-derived fuels (RDF). This group of materials regarded as an alternative fuel is derived from industrial, municipal solid and commercial wastes. The aim of this study is to evaluate the quality of waste composition, demonstrate statistically different values and the energy efficiency of the fuel derived from waste. Data on incinerated waste were collected from two different sources. The basic physical and chemical parameters of waste include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Bro żek et al (2022) investigated the RDF incineration process and showed that, for each kilogram of RDF, about 3.85 kWh (13,860 kJ) of heat can be obtained. As for emissions, each kilogram of incinerated RDF generated 12.95 mmol NOX /g RDF , 0.0328 mmol SOX /g RDF , and 49.31 mmol CO2 /g RDF [73].…”
Section: Incinerationmentioning
confidence: 99%
“…Bro żek et al (2022) investigated the RDF incineration process and showed that, for each kilogram of RDF, about 3.85 kWh (13,860 kJ) of heat can be obtained. As for emissions, each kilogram of incinerated RDF generated 12.95 mmol NOX /g RDF , 0.0328 mmol SOX /g RDF , and 49.31 mmol CO2 /g RDF [73].…”
Section: Incinerationmentioning
confidence: 99%
“…Currently, composite waste ends up in landfill or is incinerated in municipal incineration plants [16]. Landfills are the cheapest method of disposing of composite waste in Poland, but according to the Waste Framework Directive 2008/98/EC [17], it is a last resort.…”
mentioning
confidence: 99%